The Attitude of Chinese Consumers toward Illegal Downloading of Music, Movies and Software in the United States - Shen, Li; Amendah, Eklou (Journal of Comparative International Management)

(untitled) (Management Futures, 2015)
Piracy of intellectual property, and especially unauthorized downloading of music, movies and software programs, causes significant loss of revenue to US firms. While the illegal downloading of intellectual properties by Chinese consumers has been the focus of various reports published in the popular press, not much academic work on the topic has been published. This paper, based on a review of the extant literature on this topic, is an attempt to further our understanding of this phenomenon. This paper proffers several testable propositions covering a whole gamut of downloading behavior by Chinese consumers and the causes thereof. The paper concludes with a discussion on the limitations of the study followed by directions for future research that could potentially deepen our understanding of this topic.